Utilização de extrato hidrossolúvel de soja na elaboração de bebida fermentada simbiótica - Brandão, Henry (2012)
In Brazil, the grain harvest in 2007/08 was about 145 million tons, a record for the domestic agriculture. In 2008 soybeans led to participation in the value of production of temporary and permanent crops with 39.18% which were superseded by the 2009/2010, in which the Paraná state reached the first place in soybean production in Brazil. As possible benefits of diets containing soy we could mention the anticarcinogenic effects, reduction of cholesterol levels, protective effects against obesity and symptoms such as hot flashes during menopause, treatment of coronary heart disease and osteoporosis. According to this economic and health context, this work aimed the development of a hydrosoluble soybean extract fermented with probiotic microorganisms, plus inulin (prebiotic substance) and whey protein concentrate, in order to meet the consumers expectations on health, nutrition and functionality due to their symbiotic nature. Physical and chemical, microbiological, sensory analyzes and probiotic bacteria counting were carried out, considering different types of sugars such as sucrose and glucose. Twelve formulations were prepared from hydrosoluble soybean extract with whey protein concentrate and inulin, by varying the inoculated cultures (Lactobacillus acidophilus, Lactobacillus casei and SAB) and sugar (100% glucose treatment, 100% sucrose treatment, 50% glucose and 50% sucrose treatment, and 0% sugar treatment). The sensory evaluation experiment was completely randomized, applying analysis of variance-ANOVA and Means Test (Tuckey). In the fermentation process the formulation A5 (EHS 10%, 2.5% WPC, 2% inulin, sugar and inoculum SAB) presented the shortest time register, with 5 hours and 53 minutes to achieve the optimum pH. For an optimal therapeutic effect, it is estimated that the probiotic food must contain a number above than 107 CFU / mL, and all formulations reached this viable cell count during 28 days of storage, especially the Treatment A9 with an initial count of 1,20 x1014 CFU / mL. The increased acidity values reached 85 ºD, maintaining the pH value close to 4.31, which means a suitable pH. The results of the microbiological analyzes of fermented beverages were in accordance to the standards established by the Brazilian legislation, ensuring the safety of the samples. The rate of acceptance achieved by sensory evaluation of the beverages was above 70% considering the formulations A2 (EHS 10%, 2.5% WPC, 2% of inulin, 100% sucrose and L. casei inoculum) and A10 (EHS 10% 2.5% WPC, 2% of inulin, and 100% sucrose and L. acidophilus inoculum), which means that these formulations would be well accepted in the consumers market.